OLi 3 -decorated irida-graphene for high-capacity hydrogen storage: A first-principles study - Laranjeira, José A.S. [UNESP]; Elaggoune, Warda; Martins, Nicolas F. [UNESP]; Chen, Xihao; Sambrano, Julio R. [UNESP] (Elsevier, 2025)
Efficient hydrogen storage in solid-state materials is essential for next-generation energy systems, yet achieving a high gravimetric capacity with optimal adsorption characteristics remains a critical challenge. Although Li-decorated irida-graphene (IG) has shown promising hydrogen storage potential, its capacity is limited to ∼ 7wt%, which, despite exceeding the U.S. DOE target, remains inadequate for large-scale applications. Additionally, Li clustering over extended cycles may compromise adsorption efficiency and structural stability. In this study, we employ first-principles calculations to investigate the hydrogen storage potential of IG decorated with superalkali OLi 3 clusters, aiming to enhance the adsorption capacity and stability for advanced hydrogen storage technologies. Our findings show that the OLi 3 clusters exhibit a significant binding energy of −3.24 eV, which highlights its strong interaction with the IG. OLi 3 @IG complex can host up to 12H 2 molecules, with optimal maximum storage capacity of 10.00 wt%. Additionally, the release temperature (T R ) and ab initio molecular dynamics (AIMD) simulations indicate that H 2 molecules can be efficiently released at operating temperatures under ambient conditions. These results highlight the potential of OLi 3 @IG as a promising candidate for reversible hydrogen storage.